Active protection ion skin preparation method and application
By preparing an active protective ionic skin containing water, polymers, inorganic salts and water-soluble salts, and using temperature changes to regulate the cross-linking structure, the problem of damage to the flexible ionic skin under strong external forces is solved, and the protection functions of high detection range, high sensitivity and rapid response are achieved, which is suitable for robots and wearable devices.
Patent Information
- Application Number
- CN202510966782.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-14
- Publication Date
- 2025-09-23
AI Technical Summary
Existing flexible ionic skin is easily damaged under strong external forces, and it is difficult to achieve a high detection range, high sensitivity and active protection functions.
Active protective ionic skin is prepared by using a combination of water, polymers, inorganic salts and water-soluble salts through UV curing and water immersion treatment. The cross-linking structure of the material is regulated by temperature changes to achieve dynamic switching of flexibility and strength.
It maintains flexibility and a high detection range at room temperature, improves impact strength at high temperatures, responds quickly to protect robotic equipment, adapts to a variety of usage scenarios, has a wide range of material components, is low-cost, and is suitable for large-scale production.
Smart Images

Figure CN120682413A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of flexible sensors, and in particular to a preparation method and application of active protective ionic skin. Background Art
[0002] With the rapid development of artificial intelligence and humanoid robot industries, people's demand for robots to perceive the external environment is constantly increasing. Human skin perceives external forces through ion transmission. The flexible ionic skin designed with reference to the perception mechanism of human skin will produce different deformations according to the size, direction and duration of the force when subjected to external forces, affecting the ion conductivity of the material, thereby outputting different signals. According to the signal difference, the information of the external force can be perceived, showing great application potential in humanoid robot intelligent hands and other fields.
[0003] Common flexible ionic skin is mainly composed of hydrogel and has excellent flexibility, but this makes its mechanical strength poor and easily destroyed when subjected to strong external forces, resulting in a shortened working life of the ionic skin.
[0004] Generally speaking, the ability of ionic skin to resist external forces can be improved by enhancing its impact resistance or imparting self-healing properties, but both solutions have difficult-to-overcome problems; improving the impact resistance of ionic skin can significantly reduce its damage when subjected to strong external forces, but at the same time it will reduce the flexibility and elongation at break of the ionic skin, thereby reducing the detection range and sensitivity of the ionic skin device; self-healing ionic skin can gradually repair defects after being damaged by strong external forces, but the self-healing time is relatively long, usually taking more than 12 hours to heal to its initial state, and it cannot effectively cope with frequent strong external force impacts; how to develop an ionic skin that has both high detection range and high sensitivity and the ability to actively prevent strong external force impacts is still a problem that needs to be solved urgently. Summary of the Invention
[0005] In order to solve the problems raised in the above background technology, the present invention provides a preparation method and application of active protective ion skin.
[0006] To achieve the above-mentioned object, the present invention provides the following technical solutions: an active protective ionic skin, the components of which include water, polymer, inorganic salt and water-soluble salt;
[0007] In the active protective ionic skin, the content of water is 45-70 wt%, the content of polymer is 10-25 wt%, the content of inorganic salt is 5-15 wt%, and the content of water-soluble salt is 5-15 wt%.
[0008] Preferably, the polymer is prepared by polymerization of monomers and initiators, wherein the monomers are one or more of maleic acid, fumaric acid, itaconic acid, sinapic acid, caffeic acid, p-coumaric acid, cinnamic acid, acrylic acid, methacrylic acid, methyl acrylate, acrylamide, methacrylamide, N,N-dimethylacrylamide, and N,N-methylenebisacrylamide; and the initiator is one or more of α-ketoglutaric acid, 1-hydroxycyclohexylphenyl ketone, and 2-hydroxy-2-methylpropiophenone.
[0009] Preferably, the inorganic salt is one or more of zinc oxide, magnesium hydroxide, cobalt hydroxide, tin oxide, nickel hydroxide, manganese hydroxide, and barium hydroxide.
[0010] Preferably, the water-soluble salt is one or more of sodium chloride, potassium chloride, sodium sulfate, and potassium sulfate.
[0011] A method for preparing active protective ionic skin comprises the following steps:
[0012] S1, mixing monomer, water and inorganic salt in proportion, stirring at 60°C for 30-60 minutes to obtain a precursor solution;
[0013] S2, mixing the precursor solution, initiator, monomer and water-soluble salt in proportion, stirring at 60° C. for 30-60 minutes to obtain a pre-cured liquid;
[0014] S3, pouring the pre-curing liquid into a customized mold, inserting an electric heating film into the mold, curing under ultraviolet light for 60 minutes, placing the cured solid in water, soaking it at 20°C for 2 days, taking it out and drying the surface moisture to obtain the active protective ion skin.
[0015] Preferably, the heat cross-linking temperature of the active protective ion skin is 30-85°C.
[0016] An application of an active protective ion skin in a flexible sensor comprises the following steps: a layer of flexible electrodes is screen-printed on the surface of the active protective ion skin; the active protective ion skin is immersed in a packaging material solution; and after removal, the active protective ion skin is self-leveled and dried to obtain an active protective ion skin sensor. The active protective ion skin sensor can be directly used on parts of a robot, such as hands, feet, joints, and torso, that require protection and the ability to sense external information. It can also be used in wearable electronic devices.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] 1. The present invention imparts active protective functionality to flexible ionic skin through the coordinated use of resin structure design and cross-linking agents: at room temperature, the ionic skin has no obvious cross-linking structure, resulting in high flexibility and a wide sensing range. When the temperature rises, the coordination effect between the inorganic salt cations and the polar functional groups of the polymer within the ionic skin is enhanced, and a continuous polymer network is formed through the coordination bonds between the cations and the polar functional groups. This enhances the impact strength of the ionic skin while maintaining good toughness, effectively improving the service life and protective ability of the ionic skin and resolving the problem of traditional ionic skins that "flexibility and strength cannot be achieved at the same time."
[0019] 2. The active protective ionic skin prepared by the present invention has the characteristic of rapid response. When hardening protection is no longer needed and the temperature is lowered, the ionic skin can return to its soft state at room temperature within 30 seconds. When applied to robot surface perception, when the robot recognizes that it is about to face external force impact, needs self-protection, or needs to adaptively grasp hard objects or high-load grasping, it can increase the mechanical strength and hardness of the ionic skin on the body surface through active heating, thereby protecting the robot's precision equipment and the ionic skin material itself, ensuring that the equipment is stable and not easily damaged, achieving rapid switching of mechanical properties, and adapting to dynamically changing usage scenarios.
[0020] 3. By rationally regulating the proportions of components, the present invention can flexibly adjust the mechanical properties and response temperature of the material, which can not only meet the high-intensity protection requirements of robot hands, feet, joints and other parts, but also adapt to the close fit between wearable devices and human skin, taking into account the accuracy of biological signal transmission and the service life of the material.
[0021] 4. The present invention adopts a preparation method of ultraviolet curing combined with water immersion post-treatment, which has a simple and controllable process, does not require complex equipment, and has a wide range of material components and low cost, which is convenient for large-scale production.
[0022] 5. The present invention can maintain a stable mechanical property switching effect after multiple temperature cycles through the cross-linked structure inside the material, effectively improving the number of reuses and long-term working reliability of the ion skin and reducing maintenance costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:
[0024] Figure 1 This is a schematic diagram of the active protective ion skin sample of the present invention;
[0025] Figure 2The curves of the change in the ratio of the storage modulus after heating to the crosslinking temperature and then turning off the heating and the storage modulus in the initial crosslinking state are shown in the examples and comparative examples;
[0026] In the figure: 1. Active protective ionic skin layer; 2. Electric heating film; 3. Flexible electrode; 4. Encapsulation layer. DETAILED DESCRIPTION
[0027] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0028] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative work shall fall within the scope of protection of the present invention.
[0029] Example 1:
[0030] Active Protection Ionic Skin Preparation:
[0031] Maleic acid, water and zinc oxide are mixed in proportion, and stirred at 60°C for 60 minutes to obtain a precursor solution; the precursor solution, α-ketoglutaric acid, methacrylamide and sodium chloride are then mixed in proportion, and stirred at 60°C for 60 minutes to obtain a pre-curing liquid; the pre-curing liquid is poured into a customized mold, an electric heating film is inserted into the mold, and the mold is cured under ultraviolet light for 60 minutes. The cured solid is placed in water and soaked at 20°C for 2 days. After being taken out and dried, the surface moisture is obtained to obtain an active protective ionic skin; the obtained ionic skin has a water content of 62%, a polymer content of 15%, an inorganic salt content of 8%, and a water-soluble salt content of 15%.
[0032] Performance testing:
[0033] Take the active protection ion skin sample and perform a tensile test at room temperature. The tensile strength is 72kPa and the elongation at break is 2074%; the tensile test is performed at 80℃, the tensile strength is 4.7MPa and the elongation at break is 271%; the active protection ion skin sample is heated to 80℃ through an electric heating film, and after keeping warm for 5 minutes, the heating is turned off and the change in storage modulus is immediately tested. After 24 seconds, the storage modulus of the sample returns to room temperature.
[0034] Example 2:
[0035] Active Protection Ionic Skin Preparation:
[0036] Itaconic acid, water and magnesium hydroxide are mixed in proportion, and stirred at 60°C for 60 minutes to obtain a precursor solution; the precursor solution, 1-hydroxycyclohexyl phenyl ketone, acrylamide and potassium chloride are then mixed in proportion, and stirred at 60°C for 30 minutes to obtain a pre-curing liquid; the pre-curing liquid is poured into a customized mold, an electric heating film is inserted into the mold, and the mold is cured under ultraviolet light for 60 minutes. The cured solid is placed in water and soaked at 20°C for 2 days. After being taken out and dried, the surface moisture is obtained to obtain an active protective ionic skin; the obtained ionic skin has a water content of 68%, a polymer content of 13%, an inorganic salt content of 6%, and a water-soluble salt content of 13%.
[0037] Performance testing:
[0038] Take the active protection ion skin sample and perform a tensile test at room temperature. The tensile strength is 57kPa and the elongation at break is 1752%. The tensile test is performed at 50℃. The tensile strength is 3.9MPa and the elongation at break is 221%. The active protection ion skin sample is heated to 55℃ through an electric heating film. After keeping warm for 5 minutes, the heating is turned off and the change in storage modulus is immediately tested. After 17 seconds, the storage modulus of the sample returns to room temperature.
[0039] Example 3:
[0040] Active Protection Ionic Skin Preparation:
[0041] Cinnamic acid, water and barium hydroxide are mixed in proportion and stirred at 60°C for 60 minutes to obtain a precursor solution; the precursor solution, 2-hydroxy-2-methylpropiophenone, acrylamide and sodium chloride are then mixed in proportion and stirred at 60°C for 30 minutes to obtain a pre-curing liquid; the pre-curing liquid is poured into a customized mold, an electric heating film is inserted into the mold, and the mold is cured under ultraviolet light for 60 minutes. The cured solid is placed in water and soaked at 20°C for 2 days. After being taken out and dried, the surface moisture is obtained to obtain an active protective ionic skin; the obtained ionic skin has a water content of 69%, a polymer content of 11%, an inorganic salt content of 8%, and a water-soluble salt content of 12%.
[0042] Performance testing:
[0043] Take the active protection ion skin sample and perform a tensile test at room temperature. The tensile strength is 72kPa and the elongation at break is 1946%; the tensile test is performed at 35°C. The tensile strength is 1.2MPa and the elongation at break is 1021%; the active protection ion skin sample is heated to 35°C through an electric heating film. After keeping warm for 5 minutes, the heating is turned off and the change in the storage modulus is immediately tested. After 5 seconds, the storage modulus of the sample returns to room temperature.
[0044] Comparative Example 1:
[0045] Active Protection Ionic Skin Preparation:
[0046] Maleic acid, water and zinc oxide are mixed in proportion, and stirred at 60°C for 60 minutes to obtain a precursor solution; the precursor solution, α-ketoglutaric acid, methacrylamide and sodium chloride are then mixed in proportion, and stirred at 60°C for 60 minutes to obtain a pre-curing liquid; the pre-curing liquid is poured into a customized mold, an electric heating film is inserted into the mold, and the mold is cured under ultraviolet light for 60 minutes. The cured solid is placed in water and soaked at 20°C for 2 days. After being taken out and the surface moisture is wiped off, an active protective ionic skin is obtained; the obtained ionic skin has a water content of 65%, a polymer content of 7%, an inorganic salt content of 3%, and a water-soluble salt content of 25%.
[0047] Performance testing:
[0048] A sample of active protective ionic skin was taken and tensile tested at room temperature. The tensile strength was 22 kPa and the elongation at break was 957%. A tensile test was performed at 80°C. The tensile strength was 579 kPa and the elongation at break was 447%. The active protective ionic skin sample was heated to 80°C through an electric heating film. After keeping warm for 5 minutes, the heating was turned off and the change in storage modulus was immediately tested. After 25 minutes, the storage modulus of the sample returned to room temperature. Compared with Example 1, the content of polymer and inorganic salt was reduced. The ionic skin could not be effectively hardened at high temperature, and could not provide good protection at high temperature. Moreover, the speed of recovering from high temperature to room temperature was too slow, and a rapid response could not be achieved.
[0049] Comparative Example 2:
[0050] Active Protection Ionic Skin Preparation:
[0051] Maleic acid, water and zinc oxide are mixed in proportion, and stirred at 60°C for 60 minutes to obtain a precursor solution; the precursor solution, α-ketoglutaric acid, methacrylamide and sodium chloride are then mixed in proportion, and stirred at 60°C for 60 minutes to obtain a pre-curing liquid; the pre-curing liquid is poured into a customized mold, an electric heating film is inserted into the mold, and the mold is cured under ultraviolet light for 60 minutes to obtain an active protective ionic skin; the obtained ionic skin has a water content of 30%, a polymer content of 29%, an inorganic salt content of 14%, and a water-soluble salt content of 27%.
[0052] Performance testing:
[0053] Take the active protection ion skin sample and perform a tensile test at room temperature. The tensile strength is 147kPa and the elongation at break is 369%; the tensile test is performed at 80°C, the tensile strength is 6.5MPa, and the elongation at break is 75%; the active protection ion skin sample is heated to 80°C through an electric heating film, kept warm for 5 minutes, and then the heating is turned off. The change in storage modulus is immediately tested. After 30 minutes, the storage modulus of the sample returns to room temperature. Compared with Example 1, the water content is reduced, and the detection range of the ion skin at room temperature is too low, and it cannot effectively play the role of signal recognition. The elongation at break is low at high temperature, and it is fragile, and cannot play a good protective effect. In addition, the speed of recovery from high temperature to room temperature is too slow, and a rapid response cannot be achieved.
[0054] Comparative Example 3:
[0055] Active Protection Ionic Skin Preparation:
[0056] Maleic acid, water and zinc oxide are mixed in proportion, and stirred at 60°C for 60 minutes to obtain a precursor solution; the precursor solution, α-ketoglutaric acid and sodium chloride are then mixed in proportion, and stirred at 60°C for 60 minutes to obtain a pre-curing liquid; the pre-curing liquid is poured into a customized mold, an electric heating film is inserted into the mold, and the mold is cured under ultraviolet light for 60 minutes. The cured solid is placed in water and soaked at 20°C for 2 days. After being taken out and dried, the surface moisture is obtained to obtain an active protective ionic skin; the obtained ionic skin has a water content of 62%, a resin content of 15%, an inorganic salt content of 8%, and a water-soluble salt content of 15%.
[0057] Performance testing:
[0058] Take the active protection ion skin sample and do a tensile test at room temperature. The tensile strength is 63kPa and the elongation at break is 1427%; do a tensile test at 80℃, the tensile strength is 8.5MPa and the elongation at break is 27%; heat the active protection ion skin sample to 80℃ through an electric heating film, keep warm for 5 minutes, turn off the heating, and immediately test the change in storage modulus. After 55 minutes, the storage modulus of the sample returns to room temperature. Compared with Example 1, the second monomer methacrylamide is removed. The elongation at break of the ion skin is too low at high temperature and it is easy to break. It cannot play a good protective effect at high temperature, and the speed of recovery from high temperature to room temperature is too slow, and rapid response cannot be achieved.
[0059] The preferred embodiments of the present invention disclosed above are intended only to help illustrate the present invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the present invention to specific embodiments. Obviously, many modifications and variations are possible based on the contents of this specification. These embodiments are selected and described in detail in this specification to better explain the principles and practical applications of the present invention, thereby enabling those skilled in the art to better understand and utilize the present invention.
Claims
1. An active protective ionic skin, characterized by: The ingredients include water, polymers, inorganic salts and water-soluble salts; In the active protective ionic skin, the content of water is 45-70 wt%, the content of polymer is 10-25 wt%, the content of inorganic salt is 5-15 wt%, and the content of water-soluble salt is 5-15 wt%.
2. The active protective ionic skin according to claim 1, characterized in that: The polymer is prepared by polymerization of monomers and initiators, wherein the monomers are one or more of maleic acid, fumaric acid, itaconic acid, sinapic acid, caffeic acid, p-coumaric acid, cinnamic acid, acrylic acid, methacrylic acid, methyl acrylate, acrylamide, methacrylamide, N,N-dimethylacrylamide, and N,N-methylenebisacrylamide; and the initiators are one or more of α-ketoglutaric acid, 1-hydroxycyclohexylphenyl ketone, and 2-hydroxy-2-methylpropiophenone.
3. The active protective ionic skin according to claim 1, characterized in that: The inorganic salt is one or more of zinc oxide, magnesium hydroxide, cobalt hydroxide, tin oxide, nickel hydroxide, manganese hydroxide, and barium hydroxide.
4. The active protective ionic skin according to claim 1, characterized in that: The water-soluble salt is one or more of sodium chloride, potassium chloride, sodium sulfate and potassium sulfate.
5. A method for preparing active protective ionic skin, characterized by: The steps include: S1, mixing monomer, water and inorganic salt in proportion, stirring at 60°C for 30-60 minutes to obtain a precursor solution; S2, mixing the precursor solution, initiator, monomer and water-soluble salt in proportion, stirring at 60° C. for 30-60 minutes to obtain a pre-cured liquid; S3, pouring the pre-curing liquid into a customized mold, inserting an electric heating film into the mold, curing under ultraviolet light for 60 minutes, placing the cured solid in water, soaking it at 20°C for 2 days, taking it out and drying the surface moisture to obtain the active protective ion skin.
6. The method for preparing an active protective ionic skin according to claim 5, characterized in that: The heat cross-linking temperature of the active protective ion skin is 30-85°C.
7. An application of an active protective ionic skin in a flexible sensor, characterized by: The process includes the following steps: a layer of flexible electrodes is screen-printed on the surface of the active protective ion skin; the active protective ion skin is immersed in a packaging material solution; the active protective ion skin is taken out and self-leveled and dried to obtain an active protective ion skin sensor. The active protective ion skin sensor can be directly used on robot hands, feet, joints, torsos and other parts that need to be protected and perceive external information, and can also be used in wearable electronic devices.